Balance nutrition and vaccination as efforts to prevent COVID-19 in the community: A cross-sectional study - Sausan Syadza; Husnah Husnah; Sitti Hajar; Iflan Nauval; RM Agung Pranata Atmaja (Trends in Infection and Global Health, 2022)
The increasing cases of COVID-19 are worrying because of its rapid spread and fatality. Efforts are needed to prevent the spread of COVID-19, such as increasing immunity of the body by enforcing vaccination programs, fulfilling balanced nutritional intake, and increasing knowledge about balanced nutrition for the community. This is a descriptive cross-sectional study conducted from August 5 to 10, 2021. A cluster sampling technique was used to recruit respondents and 106 respondents were obtained. Perceptions of balanced nutrition and vaccination were assessed by a self-composed questionnaire while nutritional intake was assessed using the Food Frequency Questionnaire (FFQ). The results of the study showed that 89 respondents (84%) had a good perception of balanced nutrition and  55 respondents (51.9%) had a good perception of vaccinations. Seventy-nine respondents (74.5%) had a good eating habits while 61 respondents (57.5%) had received vaccination. Most participants (84%)  chose family/friends as sources of information about nutrition while (94.3%) chose mass media as an important sources of information on vaccination.